MENINGKATKAN KEMAMPUAN MENGANALISIS UNSUR INTRINSIK CERPEN MELALUI PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP SISWA SMAN UNGGUL ACEH TIMUR - Erly Yuniar Saragih (Jurnal Mahasiswa Akuntansi Samudra, 2021)
This study aims to determine the increase in learning outcomes of Indonesian language material intrinsic elements in short stories through jigsaw cooperative learning in class XI IPA-2 East Aceh Superior High School. The research conducted was classroom action research which was carried out in two cycles. Each cycle goes through the stages of planning, implementation, observation and reflection. The subjects of this study were students of class XI science at SMA Negeri Unggul Aceh Timur in semester 2 of the 2020/2021 academic year. The instruments used are observation sheets and test sheets. The results obtained in the first cycle with learning completeness of 68% (19 students) of 28 students, with an average value of 71, from the initial condition which was only 25% (7 students) with an average of 46. In the second cycle completeness learning 89% (25 students) with an average of 78. Based on the results of the study, it can be concluded that the application of jigsaw cooperative learning in Indonesian lessons material intrinsic elements in short stories can improve student learning outcomes in class XI IPA-2 East Aceh Superior High School.